2006
DOI: 10.1007/s10719-006-7926-2
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of angiogenic switch in capillary endothelial cells by cAMP: A cross-talk between up-regulated LLO biosynthesis and the HSP-70 expression

Abstract: During tumor growth and invasion, the endothelial cells from a relatively quiescent endothelium start proliferating. The exact mechanism of switching to a new angiogenic phenotype is currently unknown. We have examined the role of intracellular cAMP in this process. When a non-transformed capillary endothelial cell line was treated with 2 mM 8Br-cAMP, cell proliferation was enhanced by approximately 70%. Cellular morphology indicated enhanced mitosis after 32-40 h with almost one-half of the cell population in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…Thus, evidence linking sphingolipid biosynthesis to the machinery of N-linked glycosylation is only beginning to accumulate. Concerning the second possibility, protein kinase A was recently demonstrated to regulate N-linked glycosylation (48). Ceramides activate protein kinase A (49), but addition of an inhibitor of protein kinase A did not exhibit a phenotype similar to that evoked by treatment with FB1 (not shown).…”
Section: Discussionmentioning
confidence: 98%
“…Thus, evidence linking sphingolipid biosynthesis to the machinery of N-linked glycosylation is only beginning to accumulate. Concerning the second possibility, protein kinase A was recently demonstrated to regulate N-linked glycosylation (48). Ceramides activate protein kinase A (49), but addition of an inhibitor of protein kinase A did not exhibit a phenotype similar to that evoked by treatment with FB1 (not shown).…”
Section: Discussionmentioning
confidence: 98%
“…The importance of surface glycoproteins and N-linked glycosylation on endothelial functions in vitro and in vivo has been reported [46], [47], [48]. Pili et al, showed that Castanospermine (CST), an alpha glucosidase inhibitor, which prevents the synthesis of complex oligosaccharides, inhibits bovine pulmonary artery ECs and bovine aortic ECs in vitro , and inhibits in vivo angiogenesis and tumor growth [48].…”
Section: Discussionmentioning
confidence: 99%
“…Pili et al, showed that Castanospermine (CST), an alpha glucosidase inhibitor, which prevents the synthesis of complex oligosaccharides, inhibits bovine pulmonary artery ECs and bovine aortic ECs in vitro , and inhibits in vivo angiogenesis and tumor growth [48]. Martinez et al, demonstrated that N-glycosylation is critical for EC proliferation [46], [47], and that tunicamycin, an inhibitor of N-linked glycosylation, induces apoptosis in bovine adrenal microvascular endothelial cells [49]. The work presented here differs from the above studies in several aspects.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is expected that up- or down-regulation of the DPMS activity should reflect appropriately to the level of LLO and the glycoproteins. In fact, phosphorylation up-regulation of DPMS has increased the LLO biosynthesis and turnover [39]. These are significantly reduced in PKA-deficient CHO cells [38].…”
Section: Discussionmentioning
confidence: 99%